Analysis of modern building methods of production quality assurance - Nikohosyan, N.; Matviyevskyy, S.; Balatskiy, M. (Ways to Improve Construction Efficiency, 2015)
This paper explores the factors of the construction market, which have an impact on the development of quality management systems of construction products . We consider the classification of the organizational and technological methods and modern approaches to the management of product quality .